Gradenigo syndrome: treatment and sequels - Carvalho, Filipa (2019)
A 41-year-old female, went to emergency department for horizontal diplopia, facial pain, otorrhea, hearing loss and left otalgia, with a week of evolution. The fisical examination reveled limitation of the left eye abduction, exudate in middle left ear, abcense of facial palsy or spontaneous nystagmus. Of the complementary study carried out, the following stand out: evidence of left apical petrositis, left cavernous sinus thrombosis and partial occlusion of the petrous segment of the internal carotid artery. The medical treatment consisted of corticotherapy, wide-spectrum antibiotic therapy and antiaggregation. Surgical treatment included myringotomy at the emergency department, with collection of exudate, and mastoidectomy one week after the beginning of the treatment. In the follow-up, a complete recovery of the ocular movements of the left eye was observed, but there was a worsening of the auditory function.